RECONFIGURABLE MICROWAVE BANDSTOP FILTER USING NOVEL STEPPED IMPEDANCE RESONATOR - BAKHIT, AMINE ADOUM (2013)
The exponential growth of modern wireless communications market creates an unprecedented demand for compact-size. low-cost. high-performance and reconfigurable filter. Due to this recent development. much attention has been devoted to compact microwave reconfigurable filters. The first condition that must he met by a reconfigurable filter is that it must he capable of inducing microwave transmitters and receivers to he adaptable to multi-hand operations using a single filter. which is highly desirable in the current wireless communication technology.